Post-treatment transmissibility of Plasmodium falciparum infections: an observational cohort study - Kassahun Habtamu; Hallelujah Getachew; Ashenafi Abossie; Assalif Demissew; Arega Tsegaye; Teshome Degefa; Daibin Zhong; Xiaoming Wang; Ming-Chieh Lee; Guofa Zhou; Solomon Kibret; Christopher L. King; et al. (Malaria Journal)
Abstract Background Strengthening malaria control and expediting progress toward elimination requires targeting gametocytes to interrupt transmission. Artemisinin-based combination therapy (ACT) effectively clears Plasmodium falciparum asexual parasites and immature gametocytes but has a limited impact on mature gametocytes, which mosquitoes ingest during a blood meal. To address this gap, the World Health Organization recommends adding a single low dose of primaquine (PQ) to ACT regimens. This study assessed the efficacy of a single low-dose PQ for P. falciparum gametocyte clearance and evaluated mosquito infectiousness in Ethiopia. Methods A prospective cohort study was conducted using passive case detection to enrol individuals with uncomplicated P. falciparum malaria at six health facilities. Participants were treated with either ACT alone or ACT plus 0.25 mg/kg single-dose PQ (ACT + PQ) and followed for 28 days with weekly visits. Blood smears for parasite counts, filter paper samples for DNA isolation, and whole blood for RNA preservation were collected on days 0, 7, 14, 21, and 28. On day 7, venous blood was obtained for membrane feeding assays using the Hemotek® system to assess mosquito infection. Logistic regression analysed mosquito infection predictors, while gametocyte prevalence was compared between treatment arms using χ2 or Fisher’s exact tests. Results Of 304 screened patients, 192 were enroled, with a median age of 23 (IQR 17–30) years; 65.7% were male. Post-treatment, 11 human-to-mosquito transmission cases were identified on day 7. Participants receiving ACT + SLD-PQ were significantly less likely to be infectious on day 7 (OR 0.12, 95% CI 0.02–0.57, p = 0.008) and had a significantly reduced prevalence of gametocytes (OR 0.22, 95% CI 0.06–0.83, p = 0.026) compared to those receiving ACT alone. Conclusion A single course of low-dose primaquine (PQ) given with ACT significantly decreases the prevalence of gametocytaemia. Furthermore, membrane-feeding assays show that this combination also considerably lowers mosquito infection, confirming existing knowledge and emphasizing the promise of low-dose PQ as a successful transmission-blocking strategy in managing malaria.